Peningkatan Proses Pembelajaran Tematik Terpadu Dengan Menggunakan Model Problem Based Learning (PBL)di Sekolah Dasar - Lestari, Tri Novrianti; M, Ritawati; Rahmatina, Rahmatina (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
This studi aims to describe the improvement of thematic learning process with Problem Based Learning (PBL) model in class IV SD Santa Maria Muara Siberut. This type of research is a classroom action research using a qualitative and quantitatif apporoach. Result of research of learning plan cycle I 73,95% and increasing cycle II 91,66%. Activity aspects of teacher cycle I 74,99% and increased cycle II 91,66%. Activity aspectsof student cycle I 74,99% and increased cycle II 91,66%. Thus the use Problem Based Learning (PBL) can improve the process of integrated thematic learning in class IV SD Santa Maria Muara Siberut. keyword: learning process, thematic integrated, pbl